2010
DOI: 10.1107/s1600536810016922
|View full text |Cite
|
Sign up to set email alerts
|

3-Deoxyaconitine from the root ofAconitum CarmichaeliDebx.

Abstract: The title compound (systematic name: 8β-acet­oxy-14α-benzo­yloxy-N-ethyl-13β,15α-dihydr­oxy-1α,6α,16β-trimeth­oxy-4β-methoxy­methyl­eneaconitane), C34H47NO10, is a typical aconitine-type C19-diterpenoid alkaloid, and was isolated from the roots of the Aconitum carmichaeli Debx. The mol­ecule has an aconitine carbon skeleton with four six-membered rings and two five-membered rings, whose geometry is similar to these observed in other C19-diterpenoid alkaloids; both of five-membered rings have the envelope confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The spectroscopic data of compound 13 demonstrated that it had a planar structure and configuration identical to that of 3-deoxyaconitine. ,, However, C-1, C-2, C-3, C-5, and C-18 in 13 were shielded by about Δδ C −4.7, −4.3, −8.6, −7.7, and −2.7 ppm, respectively, as compared with the reported data for 3-deoxyaconitine in the same solvent, CDCl 3 , whereas C-19 was deshielded by about Δδ C +3.5 ppm. The H-1 resonance appeared as a broad singlet ( W 1/2 ≈ 6 Hz) in the 1 H NMR spectrum of 13 (acetone- d 6 or CDCl 3 ), while the 1 H NMR data of 3-deoxyaconitine did not include the H-1 resonance. ,, This indicated that 13 was the conformational isomer of 3-deoxyaconitine with ring A in the boat conformation, since ring A in the latter was confirmed to be in the chair conformation by X-ray crystallographic analysis . Thus, compound 13 was confirmed to be (−)-(A -b )-8β-acetoxy-14α-benzoyloxy- N -ethyl-13β,15α-dihydroxy-1α,6α,16β,18-tetramethoxyaconitane.…”
Section: Resultsmentioning
confidence: 96%
“…The spectroscopic data of compound 13 demonstrated that it had a planar structure and configuration identical to that of 3-deoxyaconitine. ,, However, C-1, C-2, C-3, C-5, and C-18 in 13 were shielded by about Δδ C −4.7, −4.3, −8.6, −7.7, and −2.7 ppm, respectively, as compared with the reported data for 3-deoxyaconitine in the same solvent, CDCl 3 , whereas C-19 was deshielded by about Δδ C +3.5 ppm. The H-1 resonance appeared as a broad singlet ( W 1/2 ≈ 6 Hz) in the 1 H NMR spectrum of 13 (acetone- d 6 or CDCl 3 ), while the 1 H NMR data of 3-deoxyaconitine did not include the H-1 resonance. ,, This indicated that 13 was the conformational isomer of 3-deoxyaconitine with ring A in the boat conformation, since ring A in the latter was confirmed to be in the chair conformation by X-ray crystallographic analysis . Thus, compound 13 was confirmed to be (−)-(A -b )-8β-acetoxy-14α-benzoyloxy- N -ethyl-13β,15α-dihydroxy-1α,6α,16β,18-tetramethoxyaconitane.…”
Section: Resultsmentioning
confidence: 96%